Prolotherapy for pain in iliocostal friction syndrome - Che Ku Bahirah, Che Ku Mat; Anwar, Suhaimi; Chai, Chau Chung (Clinical Research Centre Hospital Raja Permaisuri Bainun, 2022)
INTRODUCTION AND OBJECTIVE Iliocostal friction syndrome (ICFS) is a rare painful condition due to friction of lower ribs against iliac crest leading to irritation of soft tissues in contact with these structures. Structures damaged by iliocostal friction includes the inserting tendons and muscles. The treatment for ICFS mentioned in literature are rib compression belt, orthosis, prolotherapy and surgical removal of lower ribs. This case report illustrates the use of prolotherapy in pain management for ICFS.